Synthesis and multi-scale properties of PuO2 nanoparticles: recent advances and open questions. Issue 23 (24th October 2022) - Virot, Matthieu; Dumas, Thomas; Cot-Auriol, Manon; Moisy, Philippe; Nikitenko, Sergey I.
Abstract : The review focuses on the recent relevant progresses observed about PuO2 nanoparticle syntheses and characterizations including the recently deciphered electronic, structural and physico-chemical properties. Abstract : Due to the increased attention given to actinide nanomaterials, the question of their structure–property relationship is on the spotlight of recent publications. Plutonium oxide (PuO2 ) particularly plays a central role in nuclear energetics and a comprehensive knowledge about its properties when nanosizing is of paramount interest to understand its behaviour in environmental migration schemes but also for the development of advanced nuclear energy systems underway. The element plutonium further stimulates the curiosity of scientists due to the unique physical and chemical properties it exhibits around the periodic table. PuO2 crystallizes in the fluorite structure of the face-centered cubic system for which the properties can be significantly affected when shrinking. Identifying the formation mechanism of PuO2 nanoparticles, their related atomic, electronic and crystalline structures, and their reactivity in addition to their nanoscale properties, appears to be a fascinating and challenging ongoing topic, whose recent advances are discussed in this review.